Brute force : animal horror movies - Lennard, Dominic (SUNY series horizons of cinema, 2019)
"It's always been a wild world; humans started telling stories of killer animals as soon as they could tell stories at all. Movies are an especially popular vehicle for our fascination with fierce creatures. In Brute Force, Dominic Lennard takes a close look at a range of cinematic animal attackers, including killer gorillas, sharks, snakes, bears, wolves, and spiders--even a few dinosaurs. Lennard argues that animal horror is not so much a focused genre as it is an impulse, tapping into age-old fears of being hunted. At the same time, these films expose conflicts and uncertainties in our current relationship with animals. Movies considered include King Kong, Jaws, The Grey, Them!, Arachnophobia, Jurassic Park, Snakes on a Plane, An American Werewolf in London, and many more. Drawing on insights from film studies, art history, cognitive science, and evolutionary psychology, Brute Force is an engaging critical exploration--and appreciation--of cinema's many bad beasts"--